The healthcare burden imposed by children with gastroparesis and the shift imposed by COVID-19 - Sadaka, Christian; Xu, Binghong; Benitez, Alain; Orians, Carolyn; Pearlstein, Haley; Mousa, Hayat (Frontiers in Pediatrics, 2025)
GoalsWe aim in this study to report the trend of annual economic burden of children admitted with Gastroparesis (GP) over the last 10 years and evaluate the possible effect of COVID-19.BackgroundInpatient healthcare utilization by children with GP was last reported between 2004 and 2013. Since then, the effect of the COVID-19 pandemic has not been evaluated.StudyWe used the Pediatric Health Information System (PHIS) database to retrieve data recorded in 42 children’s hospitals between January 2014 and September 2023 with GP being a primary or secondary diagnosis.ResultsA total of 20,293 pediatric gastroparesis admissions were documented. The total cost was $1,323,541,518. The average admission cost was $65,222 and the median was $18,921. Reviewing the possible effect of COVID-19, we found that the highest annual mean and median costs were in 2020, and the highest annual total cost was in 2022. The costs are divided over 6 different categories: clinical, imaging, lab, pharmacy, supplies, and others, with the highest impacts resulting from these 3 categories: clinical, pharmacy, and others. The mean and median costs differ in the 4 regions, Northeast, South, Midwest and West, with the highest in the Midwest. Of all the admissions, 15.6% had a code for nasogastric tube (NG) present, 40.7% used the code for a gastrostomy tube (G-tube), 10.0% had a code for a jejunostomy tube (J-tube) and 24.6% required nutrition support via surgical feeding tubes.ConclusionThis PHIS database study confirms an upward trend in the annual healthcare utilization by children admitted with GP, resulting in an upward trend in the total economic burden on children's hospitals emphasized by the COVID-19 pandemic.